Pengaruh Terapi Relaksasi Meditasi terhadap Penurunan Tekanan Darah Pada Lansia dengan Hipertensi di Wilayah Binaan Rumah Sakit Emanuel Klampok Banjarnegara - Sudiarto,; Wijayanti, Rahayu; Sumedi, Taat (Jurusan Keperawatan FIKES UNSOED, 2007)
Hypertension of elderly is a systolic pressure that is equal or more than 140 mmHg and/or diastolic pressure that is equal or more than 90 mmHg. One of hypertension managements is without drug where the result is more than just only overcoming this disease but also prevent stroke and heart attack. By relaxed meditation technique whole body will rest, physical will rest, mental will rest, and improve the blood circulation to muscles so that the muscles tend to relax and the blood pressure may reduce. This study on an elderly integrated services post (Posyandu) in the region founded by Emanuel hospital at Kaliwinasuh Village Klampok subdistrict Banjarnegara Regency, from November to December 2006, aimed to fiond out the effect of relaxed meditation therapy on reduction of elderly blood pressure with hypertension. This was a pre-experimental study without control group with a one group pretest-posttest design. Sampling method used was total sampling. Respondent of this study was 30 elderly people suffering hypertension. Data collecting tool was a questionnaire (Indriyani, 2005), and observation was collected by measuring blood pressure before and after relaxed meditation. The results showed that that systolic blood pressure on the statistical test indicated that P = 0.000 (P0.05) meaning that H-a was rejected or diastolic blood pressure between before and after relaxed meditation cannot be reduced significantly. Result of the study showed that there is an effect of relaxed meditation on reduction of systolic blood pressure, however it needs a further study about this effect by using control group as comparative, or other variables such as religion, marital status, socioeconomic level.